2019
DOI: 10.1016/j.jneb.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Ripple Effect Mapping Outcomes of a Childhood Obesity Prevention Program From Youth and Adult Dyads Using a Qualitative Approach: iCook 4-H

Abstract: Objective: To describe the impact of the iCook 4-H intervention study based on data gathered through ripple effect mapping focus groups through an explorative approach. Design: YouthÀadult dyads responded about ways in which iCook had affected the individual, family, and community. Three questions were asked: (1) What were people doing differently as a result of iCook? (2) Who benefited from iCook and how? (3) Were there changes in the way community groups and institutions did things as a result of iCook? Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A qualitative impact evaluation conducted at the end of the 24-month Intervention Study is reported in this issue 83 to amplify the benefits of the Intervention Study for the treatment group. The researchers used ripple effects mapping (REM) 84 to assess program effectiveness by identifying participants' perceptions of the program's success for individuals, families, and the broader community.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative impact evaluation conducted at the end of the 24-month Intervention Study is reported in this issue 83 to amplify the benefits of the Intervention Study for the treatment group. The researchers used ripple effects mapping (REM) 84 to assess program effectiveness by identifying participants' perceptions of the program's success for individuals, families, and the broader community.…”
Section: Discussionmentioning
confidence: 99%
“…REM emerged as an evaluation method that allows researchers to map program impacts according to the community capitals framework in order to observe the "spiraling up" effect. REM has been used to evaluate poverty reduction programs (Welborn et al, 2016), youth programs (Baker & Johannes, 2013;Emery, 2013), a childhood obesity prevention program (Olfert et al, 2018(Olfert et al, , 2019, a tourism Extension program (Bhattacharyya, Templin, Messer, & Chazdon, 2017) and other community health and development programs (see Chazdon et al, 2017 for summaries). Importantly for this study, REM has also been used to evaluate an FCS volunteerism program, the Extension Wellness Ambassador Program in Arkansas (Washburn et al, 2018).…”
Section: Ripple Effect Mapping (Rem)mentioning
confidence: 99%
“…The mind mapping portion of REM allows participants to visualize these three different levels of changes, and encourages them to think through otherwise unrecognized or indirect impacts of their actions (Baker & Johannes, 2013;Kollock et al, 2012;Welborn et al, 2016). While some studies that use REM ask participants to categorize impacts according to the community capitals framework, Welborn et al (2016) and Olfert et al (2019) found that understanding the concept of community capitals can be challenging for community participants, and suggest instead that researchers use the framework to guide their analysis. While previous studies have used REM to assess the public value of interventions, and therefore look at "how the program would impact constituents who did not participate," (Haskell et al, 2019, p. 3), the current study is interested specifically in the impacts of an Extension volunteerism program on Extension's social capital assets.…”
Section: Ripple Effect Mapping (Rem)mentioning
confidence: 99%
See 1 more Smart Citation
“…A new dimension, for myself at least, is the impact evaluation using Ripple Effects Mapping as described in the first Olfert et al article. 4 Once again, these researchers provide us with more than just the results of the project in identifying and describing novel methods. As we as researchers begin to use these novel methods, they reflect the outcomes reported in this article.…”
mentioning
confidence: 99%